IMPLEMENTASI PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA - Yuyun Bahtiar; Nurul Anwar (Edudeena: Journal of Islamic Religious Education, 2020)
Abstract: The low learning outcomes of PAI grade VII A students of SMP I Megaluh Jombang, need to be improved and improved as well as finding solutions so that the quality of PAI learning increases. Through the application of learning Numbered Heads Together in learning process can encourage students to be active and directly involved in learning such as solving problems, dare to express opinions, respect the opinions of others so that learning is more alive and students are encouraged to prepare themselves well. Then it will increase attention, interest and motivate learning and encourage the creation of participatory learning. The research objective is to determine the learning outcomes of PAI and determine the supporting and inhibiting factors using NHT type learning. The study design includes planning, implementation, observation/field notes, and reflection. The research subjects of class VII A of SMP I Megaluh, odd semester of 2014/2015 were 30 students. Data collection techniques in the form of tests, observations/field notes and documentation, then the data were analyzed using qualitative descriptive statistics. The results of the management and analysis of the data can be concluded that through the application of NHT learning model in the learning process it turns out the learning outcomes about the prayers of Grade VII A students of SMP I Megaluh can be improved.